2000
DOI: 10.1021/ar9702839
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Electrochemical/Chemical Synthesis of Quantum Dots

Abstract: The "electrochemical/chemical method" (or "E/C method") is a new wet chemical method for synthesizing semiconductor quantum dots on graphite surfaces. The E/C synthesis of quantum dots composed of the generic semiconducting salt, MX, typically involves three steps: (1) electrochemical deposition of nanoparticles of the metal, M°, from a solution of metal ions, M n+ ; (2) electrochemical oxidation of these metal particles to MOn/2, and; (3) displacement of the oxygen from MOn/2 using HX (for example) to yield n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
73
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(80 citation statements)
references
References 37 publications
1
73
0
6
Order By: Relevance
“…Quantum confinement can be defined as, in nano particles whose diameter is smaller than the size of its Bohr-exciton radius the degree of freedom of particle is reduced from N to zero. [11][12][13][14][15][16] So energy levels can be modelled using particle in a box model in which the energy of different states depend on the length of the box. If there radii are on the Bohr-exciton radius, then the quantum dots are said to be in weak confinement regime and the radii less than the Bohr-exciton radius, then the quantum dots are said to be in strong confinement regime.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum confinement can be defined as, in nano particles whose diameter is smaller than the size of its Bohr-exciton radius the degree of freedom of particle is reduced from N to zero. [11][12][13][14][15][16] So energy levels can be modelled using particle in a box model in which the energy of different states depend on the length of the box. If there radii are on the Bohr-exciton radius, then the quantum dots are said to be in weak confinement regime and the radii less than the Bohr-exciton radius, then the quantum dots are said to be in strong confinement regime.…”
Section: Introductionmentioning
confidence: 99%
“…show enormous photostability over regular organic fluorophores [30][31][32][33][34]. They also display size-tunable absorption and emission properties due to quantum size effect.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, tremendous interest has arisen in the synthesis of well-dispersed and uniform-sized nanomaterials. 9,10 Nanoparticles biosynthesized by organisms, without involving the toxic solvents, strict conditions, or expensive processes that are needed in chemical methods, have become a popular subject. 11 Various nanoparticles are reported that are biosynthesized by bacteria, [12][13][14] fungi, 15,16 plants, 17,18 mammalian cells, 19 or even earthworms.…”
Section: Open Access Full Text Articlementioning
confidence: 99%